Chronic Inflammation in Non-Alcoholic Steatohepatitis: Molecular Mechanisms and Therapeutic Strategies - Luci, Carmelo; Bourinet, Manon; Leclère, Pierre S.; Anty, Rodolphe; Gual, Philippe (Frontiers in Endocrinology, 2020)
Non-Alcoholic Steatohepatitis (NASH) is the progressive form of Non-Alcoholic Fatty Liver Disease (NAFLD), the main cause of chronic liver complications. The development of NASH is the consequence of aberrant activation of hepatic conventional immune, parenchymal and endothelial cells in response to inflammatory mediators from the liver, adipose tissue and gut. Hepatocytes, Kupffer cells and liver sinusoidal endothelial cells contribute to the significant accumulation of bone-marrow derived-macrophages and neutrophils in the liver, a hallmark of NASH. The aberrant activation of these immune cells elicits harmful inflammation and liver injury, leading to NASH progression. In this review, we highlight the processes triggering the recruitment and/or activation of hepatic innate immune cells, with a focus on macrophages, neutrophils and innate lymphoid cells as well as the contribution of hepatocytes and endothelial cells in driving liver inflammation/fibrosis. On-going studies and preliminary results from global and specific therapeutic strategies to manage this NASH-related inflammation will also be discussed.